Transition metal-free aerobic oxidative cleavage of the C–N bonds of α-amino esters. Issue 23 (21st October 2019) - Tan, Shenpeng; Li, Feng; Park, Soojun; Kim, Sanghee
Abstract : A base-mediated aerobic oxidative cleavage of α-amino esters involving a hydroperoxide intermediate was reported, which represents the first example of the cleavage of the α-C–N bonds of amino acid derivatives without the aid of metal catalysts. Abstract : An efficient transition metal-free cleavage of the C–N bonds of α-amino esters under mild conditions has been developed. The reaction was performed in the presence of KO t Bu and molecular oxygen. Mechanistic studies reveal that the reaction proceeds through a base-mediated aerobic oxidative cleavage pathway involving the formation of a hydroperoxide intermediate.